Leriche Syndrome (Journal of Medicine, 2017)
Leriche syndrome is a thrombotic occlusion of abdominal aorta, extending both just above the site of aortic bifurcation and the common iliac arteries. Risk factors are hypertension, smoking, dyslipidemia, and diabetes. The symptoms include erectile dysfunction, bilateral claudication with ischemic pain. Surgical operation is usually recommended for the management.J MEDICINE July 2017; 18 (2) : 128-129